The Legal History Analysis of Filling the Position of Asymmetric Regional Head in the Special Region of Yogyakarta - Triwahyuningsih Triwahyuningsih (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This study aims to describe aspects of the legal history of filling the position of asymmetric Regional Head in the Special Region of Yogyakarta. This research is a normative legal research with a statute approach using primary and secondary legal materials and analyzed qualitatively descriptively. The results of the study indicate that the study of legal history shows that filling the position of Governor of DIY through a (asymmetric) determination does not conflict with Article 18 paragraph (4) of the 1945 Constitution and Article 18 B paragraph (1). The filling of the positions of Governor and Deputy Governor can be traced in various regional government laws that have been in force in Indonesia. In Act No. 22 of 1948 concerning the Principles of Regional Government: Article 18 paragraph (5) and (6) states: